The measurement of economic growth - Usher, Dan (Oxford, United Kingdom : Basil Blackwell Publishers, 1980)
This book is a comprehensive study of the concept and measurement of economic growth with emphasis on the problem of how to design a statistic to conform as closely as the data allow to the usage of the term in economic history and economic policy
Includes index
ijb, 19/07/2018
Loans
Keywords: Economic development; Macroeconomics methodology